Pinning effect of lattice Pb suppressing lattice oxygen reactivity of Pb-RuO2 enables stable industrial-level electrolysis - Chenhui Zhou; Lu Li; Zhaoqi Dong; Fan Lv; Hongyu Guo; Kai Wang; Menggang Li; Zhengyi Qian; Na Ye; Zheng Lin; Mingchuan Luo; Shaojun Guo (Nature Communications)
Abstract Ruthenium (Ru) is widely recognized as a low-cost alternative to iridium as anode electrocatalyst in proton-exchange membrane water electrolyzers (PEMWE). However, the reported Ru-based catalysts usually only operate within tens of hours in PEMWE because of their intrinsically high reactivity of lattice oxygen that leads to irrepressible Ru leaching and structural collapse. Herein, we report a design concept by employing large-sized and acid-resistant lattice lead (Pb) as a second element to induce a pinning effect for effectively narrowing the moving channels of oxygen atoms, thereby lowering the reactivity of lattice oxygen in Ru oxides. The Pb-RuO2 catalyst presents a low overpotential of 188 ± 2 mV at 10 mA cm−2 and can sustain for over 1100 h in an acid medium with a negligible degradation rate of 19 μV h−1. Particularly, the Pb-RuO2-based PEMWE can operate for more than 250 h at 500 mA cm−2 with a low degradation rate of only 17 μV h−1. Experimental and theoretical calculation results reveal that Ru-O covalency is reduced due to the unique 6s−2p−4d orbital hybridization, which increases the loss energy of lattice oxygen and suppresses the over-oxidation of Ru for improved long-term stability in PEMWE.